Filozoficzne i pragmatyczne ograniczenia etyki biznesu - Borkowski, Tadeusz (Annales. Etyka w Życiu Gospodarczym, 2023)
There are three working theses formulated and proved in the paper. First, business ethics as a science not wishful thinking, encounters the following, impossible to overcome, difficulties: Lack of a precise definition of business ethics, Ethical relativism, Strong competition on national, international, and global market, Shareholders’ interests vs. social responsibility of a company, Objective (based on scientific laws) limitations of business ethics, Ethical codes vs. the rules of a company, labour and employment legislation. Second, the author claims that a company cannot be treated as an ethical education institution. This kind of education should begin in a family, kindergartens, and schools. The issues of business ethics should be included into ethical education in above mentioned places. (e.g. negotiation, to keep one’s promise, to keep on schedule etc.) Third, the issue of business ethics (ethical codes) should not be restricted to a company only. It should be put into the context of sector, national, multinational, and global market.